The Relationship Between Social Support And Psychological Well-Being In Uptd Mojosari Health Center Employees - Lujeng Ardela; Windu Santoso; Duwi Basuki; Norizan Binti Baba Rahim (CV Media Inti Teknologi, 2025)
Background of study: Psychological well-being is a major concern for employees at UPTD Puskesmas Mojosari, particularly those facing high job demands. Social support plays an important role in this context.Aims and scope of paper: This study aims to identify the relationship between social support and psychological well-being among these employees. Using a quantitative approach, the study involved 44 respondents from all UPTD Mojosari Health Center employees, selected through a total sampling technique.Methods: Data were collected using questionnaires that measured both social support and psychological well-being.Result: The results indicated that a significant portion of respondents experienced low social support, which was associated with low psychological well-being. Analysis using Spearman's rho test revealed a significant correlation (p < 0.05) between social support and psychological well-being. This finding suggests that higher levels of social support are linked to better psychological well-being among employees.Conclusion: The implications of this study emphasize the importance of social support in maintaining mental and emotional health in the workplace. Therefore, there is a need to strengthen social support systems to create a healthier and more productive work environment.